Social perception and environmental risk factors for dengue in an endemic municipality in eastern Colombia: a mixed method study - Gloria Isabel Jaramillo-Ramirez; Simran Budhwar; Emily Ford; Gabriel Parra-Henao; Luis Felipe Cortes-Gonzalez; Laura Alejandra Saldarriaga-Gomez; Robert T. Jones (Scientific Reports)
Abstract With the climate changing and worsening rainfall patterns, dengue, and its vector, the Aedes spp. mosquito, are becoming an urgent matter both in Colombia and globally. The limited availability of vaccines for this arbovirus, combined with the risk of severe disease with each reinfection, means that dengue control primarily relies on targeted vector control tailored to specific areas. This study aims to analyze the social perceptions and environmental risk factors that affect mosquito presence and dengue acquisition in Restrepo, Meta, Colombia. A knowledge, attitudes and practices questionnaire, and focus groups were conducted in communities of Restrepo, and entomological indexes were calculated for the municipality. Quantitative and qualitative analysis were performed. Participants had good knowledge of arbovirus infections, but lacked specific knowledge about transmission and how best to protect themselves. Those knowledgeable of cleaning water tanks were 0.28 times as likely to have mosquitos trapped in their house than those who did not. By contrast, those that reported using bed nets were more likely to have mosquitoes in their house than those who did not, potentially due to an overestimated sense of protection or need to use a net because of their presence. There was little reported community organization to control Aedes mosquitos, and social stratum was determined to be a risk factor for mosquito presence. Participants were in favor of interventions by the Health Secretariat, especially insecticide spraying. Our findings identify areas of need for education and engagement initiatives: encouraging community responsibility and day-time bite prevention measures may empower residents to protect themselves better. This can help the Health Secretariat to guide promotion and prevention strategies by knowing the sociodemographic characteristics and popular knowledge of the inhabitants of the city of Restrepo.